Prevascularization techniques for dental pulp regeneration: potential cell sources, intercellular communication and construction strategies - Ruan, Qiao; Tan, Shenglong; Guo, Li; Ma, Dandan; Wen, Jun (Frontiers in Bioengineering and Biotechnology, 2023)
One of the difficulties of pulp regeneration is the rapid vascularization of transplanted engineered tissue, which is crucial for the initial survival of the graft and subsequent pulp regeneration. At present, prevascularization techniques, as emerging techniques in the field of pulp regeneration, has been proposed to solve this challenge and have broad application prospects. In these techniques, endothelial cells and pericytes are cocultured to induce intercellular communication, and the cell coculture is then introduced into the customized artificial vascular bed or induced to self-assembly to simulate the interaction between cells and extracellular matrix, which would result in construction of a prevascularization system, preformation of a functional capillary network, and rapid reconstruction of a sufficient blood supply in engineered tissue after transplantation. However, prevascularization techniques for pulp regeneration remain in their infancy, and there remain unresolved problems regarding cell sources, intercellular communication and the construction of prevascularization systems. This review focuses on the recent advances in the application of prevascularization techniques for pulp regeneration, considers dental stem cells as a potential cell source of endothelial cells and pericytes, discusses strategies for their directional differentiation, sketches the mechanism of intercellular communication and the potential application of communication mediators, and summarizes construction strategies for prevascularized systems. We also provide novel ideas for the extensive application and follow-up development of prevascularization techniques for dental pulp regeneration.